1999
DOI: 10.1093/humrep/14.9.2323
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between 21 amino acid endothelin, intrafollicular steroids and follicle size in stimulated cycles

Abstract: Several in-vitro studies have shown that endothelins (ET) may inhibit synthesis of progesterone and prevent luteinization of granulosa cells. In the present study, a specific radioimmunoassay was used to evaluate the correlation between concentrations of active (21 residue) ET and ovarian steroids in 47 samples of human follicular fluid (FF) following gonadotrophin stimulation for in-vitro fertilization (IVF) protocols. An isoform non-selective antibody was used in the radioimmunoassay, which recognized the C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…Our data showed a reduction in ET-1 concentration in the women who became pregnant following IVF. Some studies suggest that there was a negative correlation between the concentration of ET-1 in follicular fluid and in the number of oocytes retrieved or with AFC (Haq et al 1996) and the maturation of follicles (Plonowski et al 1999). Consistent with these studies, our data also showed that the concentration of ET-1 in follicular fluid was negatively correlated with AFC or ovary volume.…”
Section: Discussionsupporting
confidence: 91%
“…Our data showed a reduction in ET-1 concentration in the women who became pregnant following IVF. Some studies suggest that there was a negative correlation between the concentration of ET-1 in follicular fluid and in the number of oocytes retrieved or with AFC (Haq et al 1996) and the maturation of follicles (Plonowski et al 1999). Consistent with these studies, our data also showed that the concentration of ET-1 in follicular fluid was negatively correlated with AFC or ovary volume.…”
Section: Discussionsupporting
confidence: 91%
“…Their levels in the follicular fluid are significantly higher than their levels in the serum (Choi et al, 2011), suggesting that endothelins are produced endogenously. However, their levels from hyper-stimulated IVF patients are too scattered and thus endothelins are not suitable as a biomarker for the ovulation process (Plonowski et al, 1999). Therefore, we evaluated their expression levels in the GLCs.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells produce endothelins, but endothelin-1 is also expressed in ovarian cells and the peptide is present in the follicular fluid of normal women (Magini et al, 1996;Mancina et al, 1997;Iwai et al, 1993). Moreover, the concentration of endothelin-1 is negatively correlated with follicle diameter (Plonowski et al, 1999). Another endothelin peptide was recently shown to have an important ovarian function: produced by the granulosa cells around the time of ovulation, endothelin-2 affects follicular rupture and corpus luteum formation (Ko et al, 2006;Klipper et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Human [152] a-1-antitrypsin Over-expression leads to decrease oocyte quality Human [153,154] Vascular endothelial growth factor (VEGF) Over-expression leads to decrease oocyte quality and fertilization rate Human [155] Leptin Over-expression leads to decrease oocyte quality and fertilization rate Human [156][157][158] Endothelin-2 Increase oocyte maturation and fertilization rate Human [159,160] Homocystein Over-expression leads to decrease oocyte quality Human [161,162] Lactoferrin Increase oocyte quality, fertilization and cleavage rate Human [163] D-aspartic acid Increase fertilization rate Human [164] Prorenin Decrease fertilization rate Human [165] Heparan sulfate proteoglycan perlecan (HSPG) Oocyte quality, increase fertilization rate and growth factor binding and apoptosis regulation Human [59, 166,167] Fibronectin-binding protein A Cell adhesion and fertilization Human Amphiregulin, heparan sulfate proteoglycan 2; tumor necrosis factor a induced protein 6 (TNFAIP6); plasminogen, lymphatic vessel endothelial hyaluronan receptor 1, a-1-microglobulin/ bikuninprecursor (AMBP), SERPINA1, apolipoprotein A1 (APOA1) and haptoglobin (HP)…”
Section: Follicular Fluidmentioning
confidence: 99%